Relationship of Cognitive Function on Medication Adherence and Clinical Outcomes of Geriatric Patients with Diabetic Neuropathy - Muhamad Andhika Fauzi; Nadia Farhanah Syafhan; Taufan Harun Habibie (Eduvest - Journal of Universal Studies, 2025)
Diabetic neuropathy is a common complication of diabetes mellitus that significantly impacts quality of life and is also prone to cognitive decline exacerbated by diabetes complications. Medication adherence has been shown to slow or prevent cognitive decline. Neuropathy symptoms, neuropathic pain, and sensory disturbances can worsen cognitive function. This study aimed to assess the relationship between cognitive function and medication adherence, as well as clinical outcomes of neuropathy symptoms in geriatric patients with diabetic neuropathy. This observational cross-sectional study involved 217 geriatric patients at RSUD Tebet from June to September 2024. Cognitive function was assessed using the MoCA-Ina questionnaire, and adherence was measured through questionnaires, medical records, and direct observation (MARS-5, MPR, and Pill Count) as well as DNS scoring to assess clinical outcomes of neuropathy symptoms. This study found that women (71,5%) were more likely to experience cognitive decline than men (28,5%). The study found that medication adherence varied by method. Triangulation showed 64.6% non-adherence in cognitive decline versus 35.4% in normal function (OR 1.774, 95% CI: 1.001-3.144). Caregiver presence significantly affected adherence (p=0.011), with a 2.8 times higher risk of non-adherence and a 2.4 times higher risk of neuropathy symptoms in patients without caregivers.